Short Communication:Comparisons of isozyme diversity in local Java cardamom (Amomum compactum) and true cardamom (Elettaria cardamomum) - AHMAD DWI SETYAWAN; WIRYANTO WIRYANTO; SURANTO SURANTO; NURLIANI BERMAWIE; SUDARMONO SUDARMONO (Nusantara Bioscience, 2014)
Setyawan AD, Wiryanto,Suranto, Bermawie N, Sudarmono. 2014. Comparisons of isozyme diversity in local Java cardamom (Amomum compactum) and true cardamom (Elettaria cardamomum). Nusantara Bioscience 6: 94-101.Fruits of Java cardamoms (Amomum compactum) and true cardamoms (Elettaria cardamomum) had long been used as spices, flavoring agent, garnishing plants etc. This research was conducted to find out: (i) variation of isozymic bands in some population of Java cardamoms and true cardamoms; and (ii) phylogenetic relationship of these cardamoms based on variation of isozymic bands. Plant material (i.e. rhizome) of Java cardamoms was collected from Bogor Botanical Garden, and plant material of true cardamoms was gathered from Indonesian Medicinal and Aromatic Crops Research Institute, Bogor, Indonesia. Ten accessions were assayed in every population. The two isozymic systems was assayed, namely esterase (EST) and peroxidase (PER, PRX). Phylogenetic relationship was determined by UPGMA method. The results showed that esterase gave nine isozymic bands, i.e. Rf 0.15, 0.26, 0.29, 0.33, 0.38, 0.42, 0.45, 0.53, and Rf 0.58., while peroxidase gave 10 isozymic bands, i.e. Rf 0.06, 0.14, 0.18, 0.22, 0.26, 0.29, 0.32, 0.37, 0.41, and Rf 0.46. Relationship dendrogram indicated that the number of data will affect the grouping based on species similarity; and more data was increasingly apparent in groupings; within these groups there were variations among its members.